Peningkatan Minat dan Hasil Belajar Matematika melalui Model Cooperative Learning Tipe Team Games Tournament pada Siswa SD Negeri Tukangan Yogyakarta - Achmad Nur Sodiq; Trisniawati Trisniawati (AlphaMath : Journal of Mathematics Education, 2020)
The purpose of the study was to describe the increased interest and learning outcomes of students in grade II at SD Negeri Tukangan Yogyakarta. This type of research is classroom action research. The subjects of this study were the second grade students of SD Negeri Tukangan with 20 students consisting of 12 male students and 8 female students. Data analysis using descriptive analysis and quantitative analysis to determine the percentage increase in interest and learning outcomes in mathematics. The results showed that the cooperative learning model Team Games Tournament (TGT) type could increase interest and learning outcomes of students in grade II mathematics learning in mathematics at SDN Tukangan Yogyakarta. The average percentage of student interest in each aspect of the pre-cycle was 57.7% with low qualifications, increasing in the cycle I to 72.2% with medium qualifications. In cycle II it again increased to 80.2% with high qualifications. The average mathematics learning outcomes in the pre-cycle 66.48 with 30% mastery learning, increased to 71.41 in the cycle I with 70% mastery learning and in the second cycle has increased with a mean value of 79.72 with 80% completeness learning.